Effect Of Level 1 Progressive Mobilization On Oxygen Saturation In Patients With Decreased Consciousness - Karokaro, Tati Murni; Abdi Lestari Sitepu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Patients in the intensive care unit are individuals who are in critical condition due to failure of function of one or more organs, with hemodynamic instability. They require special care and intensive monitoring, in the hope that their condition can improve through appropriate medical action (Setiyawan, 2016). The incidence of stroke is increasing every year, there are 11 million stroke cases in the world, especially in low-income countries, especially in South Asian states and it causes 4 million deaths every year, around 30% of them in Southeastern countries. In addition, stroke is one of the leading causes of death and disability in adults in the United States. Every year, nearly 795,000 people in the country experience a stroke, either new or recurrent, and this causes approximately 130,000 deaths annually. (WHO, 2016). Research Objective: To understand the effect of level 1 progressive mobilization on changes in oxygen saturation in patients with decreased consciousness. Methodology: This research uses quantitative methods. The approach is quasi-experimental with a utilitarian design, where the intervention is applied to one group, then observations are made on the independent variables. Research Results and Discussion: Before progressive mobilization measures were carried out, the level 1 oxygen saturation value in patients with impaired consciousness at Grandmed Lubuk Pakam Hospital, of the 24 respondents, 2 respondents had oxygen saturation of 92% (8.3%), 4 respondents 93% (16, 7%), 7 respondents 94% (29.2%), 7 respondents 95% (29.2%), 3 respondents 96% (12.5%) and 7 respondents had oxygen saturation 98% (4.2%) . Conclusion: The average O2 saturation value in patients with decreased consciousness before doing level 1 progressive exercise was 93.33, whereas after it increased it was 95.67.